Urgensi Transformasi Terhadap Peningkatan Kualitas Pendidikan Islam - Basri Basri (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
This article focuses on the urgency of transformation towards improving the quality of Islamic education. Transformation is a change, both the policy and the education system in developing development to make the implementation and managerial of Islamic education effective in the ideal formatting of education in order to improve quality so as to be able to respond to the development of life and advancement of knowledge and technology and answer the needs of the community. From studies carried out the transformation process in the implementation of education can be increased from various aspects of the element of education, so that it can modify and formulate and reorient education according to needs